(untitled) (Research, Society and Development, 2022)
This article is a bibliographic research and aims to evaluate the occupational risks of Brazilian slaughterhouses based on the requirements established in the Regulatory Norm that deals with Safety and Health at Work in slaughterhouses and meat and derivatives processing - NR 36-, in order to establish preventive measures. This research derives from the data collected on the Labor Inspection portal that deal with the themes of work accidents and studies of the environments in the activities of the meatpacking industries. The activities with slaughter and meat derivatives are of great economic importance for Brazil, as well as constituting a high rate of work accidents correlated to inadequate conditions in these working environments. It is concluded that the safety deviations found in these working environments must be reduced or eliminated through uninterrupted prevention and control measures that can reduce overtime, the pace of work harmful to the health of the employee, errors in the identification and information of agents and risks in the workplace and failures in the use of personal protective equipment (PPE), instruments and machines. It is essential that companies comply with the legislation that ensures safety and health at work and the increase of state supervision, so that there is an advance in safety and health in these work spaces.